Security and Privacy in Dynamic Environments
DOI: 10.1007/0-387-33406-8_33
|View full text |Cite
|
Sign up to set email alerts
|

Secure Fast Handover in an Open Broadband Access Network using Kerberos-style Tickets

Abstract: In an Open Broadband Access Network consisting of multiple Internet Service Providers, delay due to multi-hop processing of authentication credentials is a major obstacle to fast handover between access points, effectively preventing delay-sensitive interactive applications such as Voice over IP. By exploiting existing trust relationships between service providers and access points, it is possible to pre-authenticate a mobile terminal to an access point, creating a Kerberos-style ticket that can be evaluated l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Jaatun, et al [10] presented a ticket method for achieving fast, secure handover in wireless OBAN (Open Broadband Access Network) consisting of multiple Internet service providers. According to their method, a ticket can be seen as a sort of letter of recommendation, where the recipient (RGW, Residential Gateway) of the ticket does not know the sender (STA); but since the recipient trusts the entity (MB, mobility broker) that created the ticket, it can also trust the sender.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Jaatun, et al [10] presented a ticket method for achieving fast, secure handover in wireless OBAN (Open Broadband Access Network) consisting of multiple Internet service providers. According to their method, a ticket can be seen as a sort of letter of recommendation, where the recipient (RGW, Residential Gateway) of the ticket does not know the sender (STA); but since the recipient trusts the entity (MB, mobility broker) that created the ticket, it can also trust the sender.…”
Section: Related Workmentioning
confidence: 99%
“…We can borrow the results in [10] to estimate the latency of re-authentication of the schemes. According to [10], the 2-way handshake between the STA and the AP takes about 5 ms in the best case, and 20 ms in the worst case. We list the comparison results in Table 2.…”
Section: General Measurements Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the related works, we found that most reauthentication mechanisms based on the Kerberos protocol [27]- [29] have the same issues regarding the modification of access points. In these approaches, the access points are modified to support processing of Kerberos credentials.…”
Section: Approaches Compromising On Deployment Costsmentioning
confidence: 99%